Chronic intestinal inflammation: inflammatory bowel disease and colitis-associated colon cancer - Rubin, Deborah C.; Shaker, Anisa; Levin, Marc S. (Frontiers in Immunology, 2012)
The inflammatory bowel diseases (IBD), including Crohn’s disease and ulcerative colitis, are chronic inflammatory disorders of the intestine. The prevalence in the United States is greater than 200 cases per 100,000, with the total number of IBD patients between 1 and 1.5 million. Crohn’s disease may affect all parts of the gastrointestinal tract, from mouth to anus, but most commonly involves the distal part of the small intestine or ileum, and colon. Ulcerative colitis results in colonic inflammation that can affect the rectum only, or can progress proximally to involve part of or the entire colon. Clinical symptoms include diarrhea, abdominal pain, gastrointestinal bleeding and weight loss. A serious long-term complication of chronic inflammation is the development of colorectal cancer. A genetic basis for IBD had long been recognized based on the increased familial risk. However, significant discordance for Crohn’s disease in twins, and a much less robust phenotypic concordance for ulcerative colitis, suggested additional factors play a role in disease pathogenesis, including environmental factors. In the past several years, progress in understanding the molecular basis of IBD has accelerated, beginning with the generation of animal models of colitis and progressing to the identification of specific genetic markers from candidate gene, gene linkage and genome wide association analyses . Genetic studies have also resulted in the recognition of the importance of environmental factors, particularly the crucial role of the gut microbiota in Crohn’s disease and ulcerative colitis. Altered immune responses to the normal intestinal flora are key factors in IBD pathogenesis. In this Research Topic, the genetic basis of IBD, the genetic and cellular alterations associated with colitis-associated colon cancer, and the emerging role of the intestinal microbiota and other environmental factors will be reviewed.